2023
DOI: 10.1097/ms9.0000000000000625
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based guideline on management of status epilepticus in adult intensive care unit in resource-limited settings: a review article

Abstract: Background: Status epilepticus (SE) is a life-threatening condition associated with at least 5 min of continuous seizures or repeated seizures without regaining consciousness between episodes. It is a medical emergency with significant morbidity and mortality. The most common causes of SE are previous seizures, stroke, trauma, metabolic disorders, and central nervous system tumor. The aim of this review was to systematically review articles and ultimately develop evidence-based guidelines for the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Despite the lack of robust randomized trials, ketamine is generally preferred as a third-line medication for RSE and SRSE. In a recent guideline for the management of status epilepticus, Besha et., al listed ketamine as class 2a, which denotes the availability of systematic reviews [ 52 ]. In addition, a survey for Canadian physicians showed that 47.4 % of physicians working with patients with SE used ketamine for the treatment of RSE [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of robust randomized trials, ketamine is generally preferred as a third-line medication for RSE and SRSE. In a recent guideline for the management of status epilepticus, Besha et., al listed ketamine as class 2a, which denotes the availability of systematic reviews [ 52 ]. In addition, a survey for Canadian physicians showed that 47.4 % of physicians working with patients with SE used ketamine for the treatment of RSE [ 53 ].…”
Section: Discussionmentioning
confidence: 99%